Kepemimpinan Karismatik dalam Membangun Pendidikan Islam yang Unggul - Erdiansyah, Erdiansyah; Khodijah, Nyayu; Febriyanti, Febriyanti (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This study aims to explore the important role of charismatic leadership in the context of Islamic education management. Using a Systematic Literature Review approach, the main objective is to investigate the contribution of charismatic leaders to inspiration, motivation, institutional identity based on Islamic values, and positive school culture.Method – The research method used is a systematic literature Review, where researchers systematically research and analyze relevant literature regarding charismatic leadership in the management of Islamic education. This approach allows researchers to compile significant findings from existing literature.Findings – The main finding of this study is that charismatic leaders have a significant impact on several aspects of Islamic education management. They can create inspiration and motivation, pioneer an institutional identity based on Islamic values, and form a positive school culture. Charismatic leaders are also able to motivate students, teachers, and school staff to achieve higher achievements, create an institutional image that is consistent with religious values, and form a positive and productive educational environment. Research Implications – The implications of this research involve a deeper understanding of the positive contribution of charismatic leadership to the quality of Islamic education. This study can be a basis for further research that deepens and further explores the influence of charismatic leaders in the management of Islamic education, as well as its impact on the formation of students' character and effective leadership. However, the limitations of this study lie in its reliance on existing literature, indicating the need for further research with more diverse methodological approaches or direct empirical data.